Comparative efficacy of antiangiogenic treatment for newly diagnosed glioblastoma: A protocol for systematic review and network meta-analysis. Issue 19 (May 2020) - Li, Runting; Li, Chao; Cai, Zhaolun; Li, Lianwang; Wei, Liudong; Qian, Zenghui; Zhou, Dabiao
Abstract: Background: Glioblastoma is the most common malignant primary brain tumor which has highly expressed vascular endothelial growth factor. To date, various antiangiogenic drugs have been investigated in clinical trials but with no overall conclusion, especially for newly diagnosed glioblastoma (nGBM). In this study, Bayesian network meta-analysis will be used to conduct a comprehensive analysis of the results of different clinical trials, and assess the efficacy of different antiangiogenic drugs on nGBM. Methods: In order to find more comprehensive information about the application of antiangiogenic drugs in nGBM patients, we searched the MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials for relevant randomized controlled trials. We also reviewed their reference lists to avoid omissions. Cochrane risk of bias tool (V.1.4.3) and Stata (V.15.0) will be used to assess the methodological quality of this review. Results: This study will provide reliable evidence for different antiangiogenic therapies in nGBM patients. Conclusion: We will evaluate the relative effectiveness of different antiangiogenic drugs and rank each intervention in nGBM patients through prognosis to provide decision-making reference on which method to choose for clinicians. Protocol registration number: CRD42019146537